Trajetórias, práticas e produção de conhecimento de intelectuais negras e negros dos Núcleos de Estudos Afro-Brasileiros da região sudeste - Isis Silva Roza (2022)
The present investigation aims to understand the trajectories, practices and production of knowledge by black women and men, intellectuals, members of the Núcleos de Estudos Afro-Brasileiros – NEABs of the Public Federal Institutions of Higher Education in the southeastern region of Brazil. The methodology procedures adopted for the research are the development of semi structured interviews and the analysis of the theoretical productions. Interviews were carried out with seven professors (women and men) members of the Núcleos de Estudos Afro-Brasileiros located in the Universidade Federal de Ouro Preto, Universidade Federal de Minas Gerais, Universidade Federal Rural do Rio de Janeiro, Universidade Federal de São Carlos, and Universidade Federal do Espírito Santo. Two theoretical productions by each black intellectual are brought to dialogues with the ones by other black intellectuals, both women and men, from other historical moments, so that we can reflect on how the themes — criticisms to hegemonic sciences and black people protagonism — have appeared in such productions. Therefore, we have built, in a collective way, an understanding of black woman and man intellectual as something diverse, but with some markers in common. Acting in the academy, arts, social movements, among other areas, they are people who take a stand in a critical way on the social reality and have their knowledge, arts, political actions, and theoretical productions anchored in the knowledge built by the Black Movement, whether they have organically taken part of it or lived its influence. The tension surrounding the perception of genders relationships and the presence of several forms of being a black intellectual, woman or man, are highlighted in this work. About the black women and men intellectuals who took part in this research, they are intellectuals grown from the experience of blackness, committed with the antiracism fight, turning to their communities and social transformation. The research points to some conclusions: the Núcleos de Estudos Afro-Brasileiros may be understood as fields for producing knowledge on the ethnic-racial relations, on the antiracism fight, of receptiveness and affection. The politization of the black human being and the participation and / or inspiration in the social movements appear as part of actions against hegemony, by black intellectuals, in the occupation of academic spaces and in the creation of epistemic cracks in the field of knowledge. As for their theoretical productions, we highlight the protagonism in remembering the action of black people and black collectivities along the history, in detriment of objectivation and simplification imposed by racism.